Cellular and Humoral Immunogenicity Investigation of Single and Repeated Allogeneic Tenogenic Primed Mesenchymal Stem Cell Treatments in Horses Suffering From Tendon Injuries - Depuydt, Eva; Broeckx, Sarah Y.; Chiers, Koen; Patruno, Marco; Da Dalt, Laura; Duchateau, Luc; Saunders, Jimmy; Pille, Frederik; Martens, Ann; Van Hecke, Lore; Spaas, Jan H. (Frontiers in Veterinary Science, 2022)
The use of mesenchymal stem cells (MSCs) for the treatment of equine tendon disease is widely investigated because of their regenerative and immunomodulatory potential. However, questions have been raised concerning the immunogenic properties of allogeneic MSCs. Therefore, two studies were conducted to assess the safety of equine allogeneic peripheral blood-derived tenogenic primed MSCs (tpMSCs). The objective was to evaluate if a single and repeated tpMSC administration induced a cellular and humoral immune response in horses suffering from tendon injuries. Horses enrolled in the first study (n=8) had a surgically induced superficial digital flexor tendon core lesion and were treated intralesionally with tpMSCs. Before and after treatment the cellular immunogenicity was assessed by modified mixed lymphocyte reactions. The humoral immune response was investigated using a crossmatch assay. Presence of anti-bovine serum albumin (BSA) antibodies was detected via ELISA. Horses enrolled in the second study (n=6) suffered from a naturally occurring tendon injury and were treated twice with tpMSCs. Blood was collected after the second treatment for the same immunological assays. No cellular immune response was found in any of the horses. One out of eight horses in the first study and none of the horses in the second study had anti-tpMSC antibodies. This particular horse had an equine sarcoid and further investigation revealed presence of antibodies against sarcoid cells and epithelial-like stem cells before treatment, which increased after treatment. Additionally, formation of antibodies against BSA was observed. These findings might indicate a non-specific immune response generated after treatment. Serum from the other horses revealed no such antibody formation. These two studies showed that the administration of tpMSCs did not induce a cellular or humoral immune response following an intralesional single or repeated (two consecutive) allogeneic tpMSC treatment in horses with tendon injury, except for one horse. Therefore, a larger field study should confirm these findings and support the safe use of tpMSCs as a therapeutic for horses suffering from tendon injuries.